The international convention for the control and management of ships' ballast water and sediments 2004: a critical appraisal - Emmanuela, Kadiri Temitope (Institute of Marine and Environmental Law, 2023)
Oceans cover more than 70 per cent of the earth's surface, and over 60 per cent of human population resides along the coast. A significant proportion of human protein supply comes from the sea, while the majority of global biodiversity and over 97 per cent of the biosphere is marine and is unknown. Invasive marine species are one of the four major threats to the world's oceans; the other three major threats are land-source marine pollution, over-exploitation of living marine resources and physical alteration and destruction of habitat.